A Climatology of the Structure, Frequency, and Propagation of Midlatitude Cyclones that Affect North Carolina - Hall, Linwood Earl, Jr. (East Carolina University, 2013)
The seasonal and interannual variability of midlatitude cyclone structure, frequency, and propagation was studied based on composites of precipitation over North Carolina. This analysis showed significant changes in the structure, frequency, and propagation of midlatitude cyclones on seasonal and interannual timescales between 1998-2010. Winter was the peak season for midlatitude cyclone passages. During winter, the strength and position of the jet aids in midlatitude cyclone formation. Summer was the least frequent in terms of midlatitude cyclone passages. The region of origin of midlatitude cyclones also had a significant effect on their structure, intensity, rainfall amounts and tracks. For all seasons, the most frequent midlatitude cyclone type was the Rockies type. This midlatitude cyclone type brought the most consistent rainfall to NC. The most intense precipitation occurred during Gulf type midlatitude cyclones. The most intense midlatitude cyclones were the Hatteras type. ENSO also played a role in midlatitude cyclone development. During El Niño events, an increase in Gulf type midlatitude cyclones occurred. During these events, intense rainfall occurred. On the other hand, during La Niña, Rockies were the dominant midlatitude cyclone type. These midlatitude cyclones brought consistent, but less intense precipitation to the SE US.
Keywords: Geography; Climatology; Midlatitude cyclones; Synoptic; Cyclones--North Carolina; Precipitation anomalies; El Niño Current; La Niña Current